Pengaruh Brand Image dan Kualitas Produk terhadap Loyalitas melalui Kepuasan Pelanggan Kopi A'Long Space Palangka Raya - Noor Aziza, Bunga; Luluk Tri Harinie; John Budiman Bancin; Gema Borneo Poetra (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This investigation aimed to analyze the relationship between brand image with product quality on customer loyalty mediated by satisfaction at Kopi A'Long Space Palangka Raya. This investigation employed a quantitative approach employing SEM-PLS analytic techniques. 100 responders who met certain criteria were included in the sample. According to this investigation, customer satisfaction and loyalty were positively and significantly impacted by brand image and product quality. Customer happiness, however, did not directly matter, and as a mediator, it was also not significant despite having a positive effect. The implication is through strengthening brand image also product quality directly.